Spatial and seasonal distribution of pesticides and clustering contamination status in a reservoir (Northeastern Mexico): Spatial analysis and multivariate approach - Briones-Escobedo, Nazdry; Rangel-Lucio, José Antonio; Benavides-González, Flaviano; Azuara-Domínguez, Ausencio; Vázquez-Sauceda, María de la Luz (Tecnología y ciencias del agua, 2024)
This study focused on the analysis of the spatial and temporal distribution of 13 pesticides in sediment and largemouth bass (Micropterus spp.) tissue, by spatial and multivariate analysis techniques in the "Vicente Guerreroâ€ dam (Tamaulipas, Mexico). The concentration of the compounds was obtained by HPLC-MS/MS using the QuEChERS extraction procedure. The mean pesticide concentration varied in sediment from 0.37 to 8.33 Âµg/kg, and in largemouth bass from 0.05 to 2.88 Âµg/kg. Spatial variation was significant at the five sampled sites, both in sediment and fish. The highest concentration and number of pesticides was recorded in the center and east of the reservoir and declined towards the landfill. The concentration of pesticides in sediment was significant (p < 0.05) throughout the evaluated period, while differences in the concentration of largemouth bass were only significant in December and May. The most frequent pesticides in sediment and tissue were amitraz, ethion, parathion, pyriproxyfen and propargite, the latter present only in the center of the dam. The results obtained suggest bioaccumulation of five pesticides from sediment to fish. Parathion is an extremely dangerous pesticide for human health and together with ethion and propargite are highly toxic to aquatic life. The results suggest carrying out frequent monitoring of the dam to detect the presence of high-risk pesticides and preserve the ecosystem health.